Reconstruction of Adult Age Regulations for Indonesian-based Population Dignity Justice - Warastuti, Yuliana Sri (KnE Social Sciences, 2025)
Adult age regulations for Indonesian residents are currently not based on dignity justice. This is because of the positive law that applies in Indonesia, where majority age is generally 18 years old. However, the provisions related to the age of adulthood or the age limit of children in Indonesia are regulated differently in laws and regulations. For this reason, it is necessary to reconstruct the adult age regulation for the Indonesian population. The formulation of the problem in this paper is: Why is the regulation of the age of adulthood for the Indonesian population currently not based on dignity justice? What are the weaknesses of the adult age regulation for the Indonesian population at this time? How reconstruction of adult age regulations for the Indonesian population based on dignity justice? Conclusion :1. Adult age regulations for the Indonesian population at this time are not based on dignity justice. 2. Weaknesses of adult age regulations for the Indonesian population at this time from the legal substance, namely, the regulation of adult age for the Indonesian population is still not uniform. The weakness of the legal structure is that there is still limited knowledge and understanding among law enforcement officials in health law. The weakness of the regulation of the adult age for the population in Indonesia at this time from the legal culture is that the legal culture in Indonesia today is still thick with the culture of “ewuh pekewuh”, the culture of maintaining people’s feelings so that they do not dare to voice the truth even though injustice occurs in front of our eyes. 3. Reconstruction of the value of justice of adult regulation for the Indonesian population based on dignity justice is to provide balanced legal protection to the entire community. The reconstruction of the legal norms of Article 150 of Law Number 1 of 2023 concerning the Criminal Code can result in adult age regulations for the Indonesian population in terms of legal benefits, legal certainty, and justice for society.